2011
DOI: 10.1016/j.jallcom.2011.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic, magnetocaloric and neutron diffraction studies on TbNi5−xMx (M=Co and Fe) compounds

Abstract: a b s t r a c tThe effect of substitution of Co and Fe for Ni in TbNi 5 on the structural, magnetic and magneto-thermal properties has been investigated. Considerable enhancement of Curie temperature is observed with Fe substitution, whereas the increase is nominal in the case of Co. Neutron diffraction measurements reveal the redistribution of moments and site preference of substitutional ions in Ni 2c and 3g sites. In TbNi 4 Fe, both Ni and Fe as well as Tb are found to carry moment while in the case of TbNi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 22 publications
0
5
0
5
Order By: Relevance
“…4 Strong electron correlations in the 4f shell of Tb were taken into account by the values of direct U ¼ 5.4 eV and exchange J ¼ 0.7 eV Coulomb interaction parameters calculated within a constrain LDA method. 6 Spin-orbit coupling was not included in these calculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Strong electron correlations in the 4f shell of Tb were taken into account by the values of direct U ¼ 5.4 eV and exchange J ¼ 0.7 eV Coulomb interaction parameters calculated within a constrain LDA method. 6 Spin-orbit coupling was not included in these calculations.…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier work we have reported the magnetic and the neutron diffraction studies of these compounds. 4 It was observed that the Ni sublattice gets partially polarized with substitution of these elements. Large enhancement of the ordering temperature, especially in the case of Fe substitution, suggests an increase in the net 3d-3d and 4f-3d exchange interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In RCo 5 and its ternary R(Co 1 À x Ni x ) 5 derivatives (x o0.7), the Co sub-lattice becomes ferromagnetic below T C [2,5,16,34]. The MEF contributed by the Co sub-lattice originates from a CurieWeiss type transition [5].…”
Section: Discussionmentioning
confidence: 99%
“…Установлено, что в соединениях семейства RNi 5 частичное замещение никеля атомами других магнитных или немагнитных элементов, трансформируя параметры электронного спектра, кристаллического поля и обменного взаимодействия, оказывает существенное влияние на транспортные и магнитные характеристики. Например, в некоторых псевдобинарных соединениях RNi 5−x M x (M -примесный элемент) обнаружены аномалии в концентрационных зависимостях структурных, электрических и термодинамических параметров, намагниченности, магнитной восприимчивости и температур фазовых переходов [8][9][10][11][12]. Такое изменение физических свойств при внедрении примеси в ряде случаев способствует улучшению функциональных характеристик материалов.…”
Section: Introductionunclassified